Melodic Intonation Therapy in Post-Stroke Non-Fluent Aphasia and Its Effects on Brain Plasticity - García-Casares, Natalia; Barros-Cano, Amanda; García-Arnés, Juan Antonio (IOAP-MPDI, 2022)
Melodic Intonation Therapy (MIT) is one of the most well-known therapies for the rehabilitation of speech in patients with non-fluent aphasia and which is thought to promote right-hemisphere involvement in language processing. This review focuses on the study of language lateralization and/or neuroplastic reorganization with neuroimaging and/or neurophysiological techniques in non-fluent aphasic patients post-stroke during or after MIT. A systematic search was carried out according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) in databases (PubMed, Scopus, EMBASE, Dialnet, Web of Science, Cochrane) with the keywords melodic intonation therapy, neuroimaging, functional magnetic resonance, and positron emission tomography and the boolean operators AND and OR. Articles including patients of all ages and either sex with any type of aphasia post-stroke and in any language, which studied language lateralization and/or neuroplastic reorganization after or during MIT were included. Articles which did not achieve the objectives, revisions and conferences were excluded. Different results were obtained from the 16 studies included in the review: predominantly greater activation of the right hemisphere but also of the left hemisphere or both. MIT is an effective therapy to rehabilitate non-fluent aphasic patients post-stroke. It involves different neurobiological mechanisms and depends on multiple individual factors. Studies with larger samples are necessary.
Keywords: Resonancia magnética; Melodic intonation therapy; Neuroimaging; Functional magnetic resonance (fMRI); Diffusion tensor imaging (DTI); Positron emission tomography (PET); Spectroscopy positron emission tomography (SPECT)